The Doll People - Martin, Ann M. 1955-; Godwin, Laura; Selznick, Brian (New York : Hyperion Books for Children, 2000)
A family of porcelain dolls that has lived in the same house for one hundred years is taken aback when a new family of plastic dolls arrives and doesn't follow The Doll Code of Honor.
Keywords: Dolls -- Fiction